VISUAL COMPOSITION IN BUILDING DRAMATIZATION OF SONG LYRICS IN THE MUSIC VIDEO “MELAWAN RESTU”: KOMPOSISI VISUAL DALAM MEMBANGUN DRAMATISASI LIRIK LAGU PADA VIDEO MUSIK “MELAWAN RESTU” - Sanjaya, William (Universitas Ciputra, 2023)
Cinematography is about combining and capturing images to form a series of images that tell a story. In practice, cinematography has several compositions, such as the rule of thirds, visual composition, and camera angles.